Neutron cross section measurements at the n_TOF facility (CERN) - Lampoudis, C.; Savvidis, E.; Papaevangelou, T.; Eleftheriadis, C.; Kitis, G.; Cano Ott, D.; Berthoumieux, E.; Dridi, W. (HNPS Advances in Nuclear Physics, 2019)
The design of innovative Accelerator Driven Systems (ADS) for incineration of nuclear waste and energy generation requires the complete knowledge of basic cross sections for neutron induced processes. The main goal of the project is to produce, evaluate and disseminate high precision cross sections for the majority of the isotopes relevant to the waste incineration and the ADS design i.e. capture and fission cross sections for the minor actinides, capture cross sections for the main fission products and (η,χη) reactions for structural and coolant materials. The most recent work, (2003-2004 campaign) took place at CERN, using a Total Absorption Calorimeter (TAC) in neutron capture measurements. The TAC was build at n_TOF facility and consists of 40 BaF2 crystals, covering an almost 4π geometry. Several targets of special interest have been measured, such as 233>234U, 241Am, 237Np, 2 4 0Pu and samples for reference and background determination as well (197Au, 2 0 8Pb, natC). Preliminary results of 2 3 7Np and 2 4 0Pu and 2 3 4U will be presented, indicating the good performance of the n_TOF facility, DAQ (Data Acquisition system) and TAC, allowing even more ambitious experiments in the future.